Inheritance law and political theology in Shakespeare and Milton : election and grace as constitutional in early modern literature and beyond - Jenkins, Joseph S. (Ashgate, 2012)
Reading God's will and a man's Last Will as ideas that reinforce one another, this study shows the relevance of England's early modern crisis, regarding faith in the will of God, to current debates by legal academics on the theory of property and its succession. Vividly treating literary and biblical battles of will, the book suggests new approaches to legal constitution informed by these dramas and by English legal history.